Digital Mental Health Resources for Asylum Seekers, Refugees, and Immigrants: Protocol for a Scoping Review - Raphiphatthana, Buaphrao (JMIR Res Protoc, 2020)
BACKGROUND: Asylum seekers, refugees, and immigrants experience a number of risk factors for mental health problems. However, in comparison to the host population, these populations are less likely to use mental health services. Digital mental health approaches have been shown to be effective in improving well-being for the general population. Thus, they may provide an effective and culturally appropriate strategy to bridge the treatment gap for these populations vulnerable to mental health risks. OBJECTIVE: This paper aims to provide the background and rationale for conducting a scoping review on digital mental health resources for asylum seekers, refugees, and immigrants. It also provides an outline of the methods and analyses, which will be used to answer the following questions. What are the available digital mental health resources for asylum seekers, refugees, and immigrants? Are they effective, feasible, appropriate, and accepted by the population? What are the knowledge gaps in the field? METHODS: The scoping review methodology will follow 5 phases: identifying the research question; identifying relevant studies; study selection; charting the data; and collating, summarizing, and reporting the results. Searches will be conducted in the following databases: EBSCOhost databases (CINAHL Plus with Full Text, MEDLINE with Full Text, APA PsycArticles, Psychology and Behavioral Sciences Collection, and APA PsycInfo), PubMed, and Scopus. Additionally, OpenGrey, Mednar, and Eldis will be searched for gray literature. All primary studies and gray literature in English concerning the use of information and communication technology to deliver services addressing mental health issues for asylum seekers, refugees, and immigrants will be included. RESULTS: This scoping review will provide an overview of the available digital mental health resources for asylum seekers, refugees, and immigrants and describe the implementation outcomes of feasibility, acceptability, and appropriateness of such approaches for those populations. Potential gaps in the field will also be identified. CONCLUSIONS: As of February 2020, there were no scoping reviews, which assessed the effectiveness, feasibility, acceptability, and appropriateness of the available digital mental health resources for asylum seekers, refugees, and immigrants. This review will provide an extensive coverage on a promising and innovative intervention for such populations. It will give insight into the range of approaches, their effectiveness, and progress in their implementation. It will also provide valuable information for health practitioners, policy makers, and researchers working with the population. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): PRR1-10.2196/19031